Sibling moderation of young adult psychological distress during a crisis: Evidence from the United Kingdom's first Covid-19 lockdown - Lisa Waddell; Susan Harkness (University of Essex, Institute for Social and Economic Research (ISER), 2022)
Young adults often rely on their parents following a crisis, and it is difficult to identify how families may mitigate any adverse emotional effects of moving home. The shock of UK Covid-19 lockdown policy, which negatively impacted all young adults, provides an opportunity to investigate how living with parents and siblings impact young men's and women's mental health during periods of adversity. By linking Millennium Cohort Study mainstage data to the Covid-19 survey, siblings appeared to moderate levels of psychological distress among young men during the lockdown, but not for young women.
Keywords: 330; Covid-19; young adults; siblings; psychological distress; crisis